2011
DOI: 10.3138/cpp.37.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of Cigarette Taxes on Birth Outcomes

Abstract: Employing provincial data from 1979 to 2004 allows us to exploit the significant (45 percent to 60 percent) reduction in excise taxes in Eastern Canada enacted in February 1994 to estimate the impacts of cigarette taxes on birth outcomes. Empirical estimates suggest that an increase in cigarette taxes is significantly associated with lower infant mortalities. However, we also find some evidence of a counter-intuitive positive correlation between taxes and fetal deaths. Overall, conditional on methodology, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“… 39 , 53 Tobacco taxes were associated with a decreased risk of infant mortality in two studies assessing this association. 57 , 60 In one of these studies, however, an increase in fetal deaths was also observed. 60 One study showed significant reductions in paediatric asthma prevalence following tobacco tax increases.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“… 39 , 53 Tobacco taxes were associated with a decreased risk of infant mortality in two studies assessing this association. 57 , 60 In one of these studies, however, an increase in fetal deaths was also observed. 60 One study showed significant reductions in paediatric asthma prevalence following tobacco tax increases.…”
Section: Resultsmentioning
confidence: 91%
“…Risk of bias of individual studies is reported in detail in the appendix (pp 32, 33) . For the EPOC studies, risk of bias was low in 23 studies, 16 , 17 , 18 , 28 , 30 , 31 , 32 , 33 , 36 , 37 , 39 , 40 , 44 , 45 , 46 , 47 , 48 , 51 , 52 , 53 , 58 , 63 , 64 moderate in 16, 19 , 34 , 35 , 41 , 42 , 43 , 49 , 50 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 and high in two. 29 , 38 For the non-EPOC studies, risk of bias was high for two studies 66 , 67 and unclear for one.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations